(untitled) (Per Musi, 2018)
This paper presents some thoughts on the repertoire developed in the curricular component keyboard and their contributions to the initial training of music teachers. Developed in group lessons, part of this repertoire is analyzed and applied through activities performed in the component pertaining to curriculum of the Bachelor’s Degree in Music at the State University of Feira de Santana. They are objects of analysis three methods: 1) Diorama ‐ Cacilda Borges Barbosa (preparatory documents); 2) 13 Small Parts Brazilian ‐Moema Craveiro Fields; 3) Miniatures (piano pieces) ‐ Mary Grace Santos. As a result, it appears that the domain knowledge and musical practices is critical to the teaching practice in the area, as the music making is an essential tool for music education. However, music making was extended from the joint with theoretical knowledge.